Review of Islamic Branding in Building Islamic Financial Literacy and Religious Behavior on Sharia Financing Preferences (Study on Employees of Pandu Holding Company) - Agus Yulianto; Indra Siswati (Universitas Mercu Buana, 2023)
Study this aim for know the effect of of islamic financial literacy and religious behavior on islamic financing preferences with islamic branding as a mediation variable. The method in this study uses primary data collected using online questionnaires through the Google form and distributed by distributing Google links to respondents to Pandu Holding Company (PHC) employees . The sampling technique used simple random sampling technique with a quantity of 30 respondents. The data analysis technique used in this study is using Structural Equation Modeling (SEM) version 3.0. The first stage, testing the validity of the questions from each variable along with its reliability. In the second stage, testing the causality of financial literacy and religious behavior towards sharia financing preferences with Islamic branding as a mediating variable. The results of this study indicate that the variables of Islamic financial literacy and religious behavior have a positive and significant effect on Islamic financing preferences through Islamic branding.